Storytelling in jazz and musicality in theatre : through the mirror - Bjerstedt, Sven (Routledge, 2021)
"Art forms tend to mirror themselves in each other. In order to understand literature and fine arts better, we often turn to music, speaking of the 'tone' in a book and of the 'rhythm' in a painting. In attempts to understand music better, we turn instead to the narrative arts, speaking of the 'story' of a musical piece. This book focuses on two examples of such conceptual mirror reflexivity: narrativity in jazz music and musicality in spoken theatre. These intermedial metaphors are shown to be significant to the practice and reflection of performing artists through their ability to mediate holistic views of what is considered to be of crucial importance in artistic practice, analysis, and education. This exploration opens up possibilities for new theoretical and practical insights with regard to how the borderland between temporal art forms can be conceptualized. The book will be of interest not only to scholars of music and theatre, but also to those who work in the fields of aesthetics, intermedial studies, cognitive linguistics, arts theory, communication theory, and cultural studies"--